Method for coating sodium electrode layered oxide positive electrode material by using nickel-manganese-titanium-copper mixture

By forming a stable P2-phase nanocoating layer on the surface of the sodium-ion battery, the cycle stability problem caused by Mn2O3 coating was solved, and the long-term stability and high-efficiency charge-discharge performance of sodium-ion batteries under high voltage were achieved.

CN121709574APending Publication Date: 2026-03-20CENT SOUTH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511859254.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-12-10
Publication Date
2026-03-20

AI Technical Summary

Technical Problem

In the existing technology, the sodium-ion electrode material coated with Mn2O3 exhibits poor cycling stability at voltages above 4.2V, with a decrease in initial charge-discharge capacity, and shows capacity ramp-up and structural instability issues during high-voltage cycling.

Method used

A stable P2-phase nanocoating layer is formed by in-situ coating of sodium-ion layered oxide cathode material with the molecular formula Naa(NixMnyTizA1-xyz)O2, where 0.5≤a≤0.85, 0.1≤x≤0.3, 0.5≤y≤0.7, 0.05≤z≤0.2, and A=Ca, Mg, Cu or Zn, using a nickel-manganese-titanium-copper mixture.

Benefits of technology

It improves the cycle stability and sodium-ion conductivity of sodium-ion battery cathode materials under high voltage, with a charge-discharge capacity retention rate of over 96% and significantly improved long-term cycle performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121709574A_ABST
    Figure CN121709574A_ABST
Patent Text Reader

Abstract

The invention discloses a method for coating a sodium electrode layered oxide positive electrode material by using a nickel-manganese-titanium-copper mixture, which is characterized in that a certain amount of nickel is added on the basis of a manganese dioxide or manganese sesquioxide coating material, so that when a P2 phase is formed by in-situ coating of the sodium electrode layered oxide positive electrode material, the nickel-manganese-titanium-copper mixture is added into the nickel-manganese-titanium-copper mixture; the charge-discharge capacity of the P2 phase and the conductivity of sodium ions in the coating layer are effectively increased, and a certain amount of titanium and elements such as magnesium, calcium, copper and zinc with large ion radiuses are added, so that the structural stability of the P2 phase is increased. The raw materials of the elements are prepared according to the molar ratio and then fully mixed to be used for coating the sodium electrode layered oxide positive electrode material, and after sintering is conducted at a certain temperature and for a certain time, in-situ reaction can be conducted on the surface of the sodium electrode layered oxide and surface residual sodium to generate a P2-phase nanometer coating layer with the structure more stable than that of a base body.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of sodium-ion battery cathode material technology, and in particular, to a method for coating sodium-ion battery layered oxide cathode material with a nickel-manganese-titanium-copper mixture. Background Technology

[0002] Sodium-ion batteries have attracted widespread attention in recent years due to their advantages such as high operating voltage, high energy density, good rate performance, excellent high and low temperature performance, and abundant sodium resources. Sodium-ion battery cathode materials have the same crystal structure as lithium cobalt oxide and ternary lithium-ion battery cathode materials, and are considered the most promising sodium-based battery material system for potentially partially replacing lithium-ion batteries. Compared with their corresponding lithium-ion battery cathode materials, the ionic radius of sodium ions is larger than that of lithium ions. This results in sodium-ion battery cathode materials exhibiting high specific capacity at voltages above 4.2V, but poor cycle stability at higher voltages.

[0003] The most direct and effective way to improve the cycle performance of battery materials is to coat the material surface with a coating layer. The coating methods for lithium-ion battery cathode materials mainly include dry coating, wet coating, and vapor deposition coating. Among these, dry coating is currently the most widely used process in the industry due to its relatively simple process, low cost, and good results.

[0004] Commonly used coating materials for lithium-ion battery cathodes include Al2O3, TiO2, Mn2O3, MgO, ZrO2, WO3, and AlPO4, all of which provide good coating effects. Sodium-ion battery cathode materials have higher sodium activity, leading to more severe surface alkali residue issues. Furthermore, sodium ions are less effective at combining with other elements than lithium ions. Therefore, based on current experimental results, the coating effect of ordinary materials is significantly inferior to that of lithium-ion battery cathode materials. Among the coating experiments of sodium-ion layered oxide cathode materials, only Mn2O3 coating currently exhibits good cycle stability, but it also has several problems. First, the initial charge-discharge capacity of the material after Mn2O3 coating is significantly reduced. Second, the capacity steadily increases in the following weeks after the initial charge-discharge cycle, with an increase exceeding 3 mAh / g. More importantly, the sodium-ion layered oxide cathode material coated with Mn2O3 exhibits normal cycling performance initially under full charge, but suddenly drops in capacity after 700 cycles. The emergence of these problems may be due to the fact that when Mn2O3 is coated, it can react with residual sodium on the surface of the oxygen-coated cathode material to form a P2 phase mainly composed of manganese and sodium. This phase has a certain stability above 4.2V, but the sodium ion conductivity of this P2 phase material is relatively low, and its structural stability will deteriorate during long-term contact with the electrolyte. At present, it seems that coating with Mn2O3 cannot meet the cycle requirements of sodium-ion batteries above 4.2V. Summary of the Invention

[0005] The purpose of this invention is to provide a method for coating sodium-ion battery layered oxide cathode materials with a nickel-manganese-titanium-copper mixture, in order to solve the technical problems that the commonly used Mn2O3 coating in the prior art cannot meet the cycle requirements of sodium-ion batteries above 4.2V.

[0006] To achieve the above objectives, the present invention provides a P2 phase nanocoating layer with the molecular formula Na. a (Ni x Mn y Ti z A 1-x-y-z O2, where 0.5≤a≤0.85, 0.1≤x≤0.3, 0.5≤y≤0.7, 0.05≤z≤0.2, and A=Ca, Mg, Cu or Zn.

[0007] This invention provides the application of the aforementioned P2 phase nanocoating layer in the preparation of sodium-electric layered oxide cathode materials.

[0008] This invention provides a method for coating sodium-ion battery layered oxide cathode materials with a nickel-manganese-titanium-copper mixture, the specific steps of which are as follows: S1. First, determine the molar ratio of each element according to the molecular formula of the aforementioned P2 phase nanocoating layer, then determine the weight ratio of the raw materials containing these elements, mix them thoroughly, and obtain the nanocoating material. S2. The nano-coating material is thoroughly mixed with the O3 structure matrix and sintered. The nano-coating material reacts in situ with the residual sodium on the surface of the O3 structure matrix to obtain a sodium-electric layered oxide cathode material coated with the aforementioned P2 phase nano-coating layer.

[0009] Preferably, in step S1, the raw material is an oxide, hydroxide, or carbonate to ensure that a layered P2 phase is formed when it reacts with residual sodium on the substrate surface.

[0010] Preferably, in step S1, the ratio is such that when reacting with a certain amount of sodium, a stable P2 phase is formed under high voltage.

[0011] Preferably, in step S1, the particle size of the raw material is no greater than 200 nm.

[0012] Preferably, in step S2, the matrix is ​​selected from any of the following: Na 0.92 (Ni 0.38 Mn 0.45 Ti 0.09 Cu 0.06 Zn 0.02 O2, Na 0.94 (Ni 0.32 Mn 0.45 Ti 0.08 Cu 0.15 O2, Na0.92 (Ni 0.33 Mn 0.54 Cu 0.08 Zn 0.04 )O2、Na1(Ni 0.2 Fe 0.22 Mn 0.45 Cu 0.13 )O2.

[0013] More preferably, the matrix is ​​prepared by the following method: determining the weight ratio of raw materials according to the molar ratio of elements, mixing them thoroughly, and sintering them in an air atmosphere.

[0014] More preferably, the raw materials for each element are: sodium carbonate for Na, hydroxide precursors for Ni and Mn, titanium dioxide for Ti, copper oxide for Cu, and zinc oxide for Zn.

[0015] A further preferred sintering condition is: first, heat to 550°C and hold for 5 hours, then heat to 850–975°C and hold for 15 hours.

[0016] Preferably, in step S2, the amount of nano-coating material used is 0.3 to 5% of the matrix mass.

[0017] Preferably, in step S2, sintering is carried out in an air or oxygen atmosphere.

[0018] Preferably, in step S2, the sintering conditions are: first, raise the temperature to 300-450°C and hold for 1.5-4 hours, then raise the temperature to 550-700°C and hold for 5-10 hours.

[0019] The present invention has the following beneficial effects: This invention provides a method for coating sodium-ion layered oxide cathode materials using a nickel-manganese-titanium-copper mixture. Based on manganese dioxide or manganese trioxide coating materials, a certain amount of nickel is added. The purpose is to effectively increase the self-charge-discharge capacity of the P2 phase and the conductivity of sodium ions in the coating layer when the sodium-ion layered oxide cathode material is in-situ coated to form the P2 phase. A certain amount of titanium and elements with larger ionic radii such as magnesium, calcium, copper, and zinc are added to increase the structural stability of the P2 phase. The final composition ratio must ensure that a stable P2 phase can be formed under high voltage when reacting with a certain amount of sodium. After the above-mentioned raw materials are prepared in molar ratios and thoroughly mixed, they can be used to coat the sodium-ion layered oxide cathode material. After sintering at a certain temperature and time, a thin P2 phase layer with the following molecular formula (Na) can be formed on the surface of the sodium-ion layered oxide through an in-situ reaction with sodium. a (Ni x Mn y Ti z A 1-x-y-zO2, where 0.5≤a≤0.85, 0.1≤x≤0.3, 0.5≤y≤0.7, 0.05≤z≤0.2, and A=Ca, Mg, Cu or Zn.

[0020] Based on existing experimental results, the stability of the cathode material matrix and the development of the coating material are crucial for the stable cycling of layered oxide sodium electrodes at higher voltages (4.3V for coin charge and above 4.25V for full charge). Previous research indicates that while Mn2O3-coated sodium electrode oxide cathode materials exhibit good performance, they still suffer from problems such as low initial charge / discharge capacity, a continuous increase in capacity after the initial charge / discharge, and a sudden drop in capacity during 4.25V cycling at full charge. To overcome these issues, this invention optimizes the composition of the coating material. The manganese content is above 50% but not exceeding 70%, ensuring the formation of a nanometer-thick P2 phase coating layer during in-situ coating. A certain amount of nickel is added to further improve the sodium-ion conductivity of the coating layer, thereby enhancing its charge / discharge capacity. A certain amount of titanium and small amounts of calcium, magnesium, copper, and zinc are added to improve the structural stability of the coating layer. By coating sodium-ion oxide cathode materials with a pre-designed nanoscale mixture, a more stable nanoscale coating layer is formed in situ during sintering, which is of great significance for improving the stability of the material during electrochemical cycling. The nickel-manganese-titanium series sodium-ion oxide cathode materials coated with the nanoscale mixture of this invention exhibit a true retention rate of over 96% after 50 cycles of 4.3V / 1C charge-discharge cycling with a coin charge, and a retention rate of over 80% after 1700 cycles of 4.25V / 1C charge-discharge cycling with a full charge.

[0021] The innovation of this invention lies in the fact that, during the coating process, not only must the sodium-electric layer oxygen P2 phase be formed in situ, but the designed composition must also ensure that the P2 phase has sufficient stability under high voltage.

[0022] In addition to the objectives, features, and advantages described above, the present invention has other objectives, features, and advantages. The invention will now be described in further detail with reference to the figures. Attached Figure Description

[0023] The accompanying drawings, which form part of this application, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an undue limitation of the invention. In the drawings: Figure 1 A mixture of nickel, manganese, titanium, and copper is used to coat the layered oxide cathode material Na for sodium-ion batteries. 0.92 (Ni 0.38 Mn 0.45 Ti 0.09 Cu 0.06 Zn 0.02 X-ray diffraction pattern of O2; Figure 2 Na, a sodium-ion battery cathode material prepared by coating 1% mixed oxides. 0.92 (Ni 0.38 Mn 0.45 Ti 0.09 Cu 0.06 Zn 0.02 Results of button cell test for O2 under charge / discharge conditions of 2.0-4.3V; Figure 3 A mixture of nickel, manganese, titanium, copper, and zinc was used to coat the layered oxide cathode material Na for sodium-ion batteries. 0.92 (Ni 0.38 Mn 0.45 Ti 0.09 Cu 0.06 Zn 0.02 X-ray diffraction pattern of O2; Figure 4 Sodium-ion battery cathode material Na prepared by coating with 2.5% mixed oxides 0.92 (Ni 0.38 Mn 0.45 Ti 0.09 Cu 0.06 Zn 0.02 Results of button cell test for O2 under charge / discharge conditions of 2.0-4.3V; Figure 5 Sodium-ion battery cathode material Na prepared by coating with 2.5% mixed oxides 0.92 (Ni 0.38 Mn 0.45 Ti 0.09 Cu 0.06 Zn 0.02 Results of full electrical cycling of O2 under charge-discharge conditions of 2.0-4.25V 1C; Figure 6 AlPO4-coated Na, a layered oxide cathode material for sodium-ion batteries 0.92 (Ni 0.38 Mn 0.45 Ti 0.09 Cu 0.06 Zn 0.02 X-ray diffraction pattern of O2; Figure 7 Na, a sodium-ion battery cathode material prepared by coating AlPO4. 0.92 (Ni 0.38 Mn 0.45 Ti 0.09 Cu 0.06 Zn 0.02 Results of button cell test for O2 under charge / discharge conditions of 2.0-4.3V; Figure 8Mn2O3 coating of Na, a layered oxide cathode material for sodium-ion batteries 0.92 (Ni 0.38 Mn 0.45 Ti 0.09 Cu 0.06 Zn 0.02 X-ray diffraction pattern of O2; Figure 9 Na, a sodium-ion battery cathode material prepared by coating with 2% Mn2O3. 0.92 (Ni 0.38 Mn 0.45 Ti 0.09 Cu 0.06 Zn 0.02 Results of button cell test for O2 under charge / discharge conditions of 2.0-4.3V; Figure 10 Na, a sodium-ion battery cathode material prepared by coating with 2% Mn2O3. 0.92 (Ni 0.38 Mn 0.45 Ti 0.09 Cu 0.06 Zn 0.02 Results of full electric cycling of O2 under charge-discharge conditions of 2.0-4.25V 1C. Detailed Implementation

[0024] The embodiments of the present invention will be described in detail below with reference to the accompanying drawings. However, the present invention can be implemented in many different ways as defined and covered by the claims.

[0025] Example 1: S1: First, based on the molecular formula Na of the nano-coating layer... 0.67 (Ni 0.25 Mn 0.55 Ti 0.10 Cu 0.10 The molar ratio of nickel, manganese, titanium, and copper is determined to be 25:55:10:10. All raw materials are selected from nanoscale oxides, and the D of all oxides is required to be... 50 All particles are around 50nm, and efforts are made to ensure that the particle size of all oxides is not too different. The proportions of each raw material are determined according to the molar ratio of the elements, and after thorough mixing, they are used as coating materials for later use.

[0026] S2: Preparation of Na-based O3 structured sodium-ion layered oxide cathode material for coating 0.92 (Ni 0.38 Mn 0.45 Ti 0.09 Cu 0.06 Zn 0.02In the preparation of the cathode material, sodium is replaced by Na2CO3, nickel and manganese by hydroxide precursors, titanium by TiO2, copper by CuO, and zinc by ZnO. The weight ratio of the raw materials is determined according to the molar ratio of the elements. After thorough mixing, the mixture is placed in a sintering furnace and sintered in an air atmosphere. The temperature is first raised to 550℃ and held for 5 hours, then raised to 950℃ and held for 15 hours. After cooling in the furnace, the single-crystal sodium-ion layered oxide cathode material is obtained.

[0027] S3: Na, a sodium-coated oxygen cathode material 0.92 (Ni 0.38 Mn 0.45 Ti 0.09 Cu 0.06 Zn 0.02 Using the amount of O2 as a reference, the amount of coating material is 1% of the matrix mass. After the matrix material and coating material are thoroughly mixed, they are placed in a sintering furnace for sintering.

[0028] S4: Sintering is carried out in an air atmosphere. First, the temperature is raised to 450℃ and held for 3 hours. Then, the temperature is raised to 650℃ and held for 6 hours to obtain sodium-ion layered oxide cathode material coated with P2 phase nano-coating.

[0029] Figure 1 The sodium-ion battery layered oxide cathode material Na, prepared under the above process conditions, is a mixture of nickel, manganese, titanium, and copper coated with a nickel-manganese-titanium-copper mixture. 0.92 (Ni 0.38 Mn 0.45 Ti 0.09 Cu 0.06 Zn 0.02 The X-ray diffraction pattern of O2 shows that the space group of the main phase of the coated sodium-ion battery cathode material is R-3m, belonging to a rhombohedral lattice crystal with lattice constants: a=b=0.297nm, c=1.61nm, α=β=90°, γ=120°. This is a typical O3 structure. To the left of the first main peak, around 16°, a very small diffraction peak appears. This peak matches the strongest peak of the P2 phase very well, likely indicating that the mixed oxide reacted in situ with residual sodium on the oxygen layer surface during coating, forming a sodium-deficient P2 phase.

[0030] Figure 2 Na is a sodium-ion battery cathode material prepared by coating 1% mixed oxide under the above process conditions. 0.92 (Ni 0.38 Mn 0.45 Ti 0.09 Cu 0.06 Zn 0.02The coin cell cycle test results for O2 under charge-discharge conditions of 2.0-4.3V showed that the 0.1C charging capacity reached 174.35 mAh / g, and the discharge capacity reached 174.09 mAh / g. The initial efficiency at 0.1C charge-discharge reached 99.85%, the initial discharge capacity at 1C was 160.09 mAh / g, and the discharge capacity at 1C for 50 cycles was 150.06 mAh / g. The actual retention rate after 50 cycles reached 95.7%. The 1C / 0.1C discharge rate was 91.96%. These results indicate that when the sodium electrode layer oxygen cathode material is coated with a small amount of nickel, manganese, titanium, and copper, its coin cell 1C cycle retention rate is significantly improved, and its overall electrochemical performance is outstanding.

[0031] Example 2: S1: First, based on the molecular formula Na of the nano-coating layer... 0.67 (Ni 0.21 Mn 0.55 Ti 0.12 Cu 0.08 Zn 0.04 The molar ratio of nickel, manganese, titanium, copper, and zinc is determined to be 21:55:12:8:4. All raw materials are selected from nanoscale oxides, and the D of all oxides is required to be... 50 All particles are around 50nm, and efforts are made to ensure that the particle size of all oxides is not too different. The proportions of each raw material are determined according to the molar ratio of the elements, and after thorough mixing, they are used as coating materials for later use.

[0032] S2: Preparation of Na-based O3 structured sodium-ion layered oxide cathode material for coating 0.92 (Ni 0.38 Mn 0.45 Ti 0.09 Cu 0.06 Zn 0.02 In the preparation of the cathode material, sodium is replaced by Na2CO3, nickel and manganese by hydroxide precursors, titanium by TiO2, copper by CuO, and zinc by ZnO. The weight ratio of the raw materials is determined according to the molar ratio of the elements. After thorough mixing, the mixture is placed in a sintering furnace and sintered in an air atmosphere. The temperature is first raised to 550℃ and held for 5 hours, then raised to 950℃ and held for 15 hours. After cooling in the furnace, the single-crystal sodium-ion layered oxide cathode material is obtained.

[0033] S3: Na, a sodium-coated oxygen cathode material 0.92 (Ni 0.38 Mn 0.45 Ti 0.09 Cu 0.06 Zn 0.02 The amount of O2 is used as a reference, and the amount of coating material is 2% of the mass of the matrix. After the matrix material and coating material are thoroughly mixed, they are placed in a sintering furnace for sintering.

[0034] S4: Sintering is carried out in an air atmosphere. First, the temperature is raised to 450℃ and held for 3 hours. Then, the temperature is raised to 650℃ and held for 6 hours to obtain sodium-ion layered oxide cathode material coated with P2 phase nano-coating.

[0035] Figure 3 The sodium-ion battery layered oxide cathode material Na, prepared under the above process conditions, is a mixture of nickel, manganese, titanium, copper, and zinc coated with a specific alloy. 0.92 (Ni 0.38 Mn 0.45 Ti 0.09 Cu 0.06 Zn 0.02 The X-ray diffraction pattern of O2 shows that the space group of the main phase of the coated sodium-ion battery cathode material is R-3m, belonging to a rhombohedral lattice crystal with lattice constants: a=b=0.297nm, c=1.61nm, α=β=90°, γ=120°. This is a typical O3 structure. To the left of the first main peak, around 16°, a very small diffraction peak appears. This peak matches the strongest peak of the P2 phase very well, likely indicating that the mixed oxide reacted in situ with residual sodium on the oxygen layer surface during coating, forming a sodium-deficient P2 phase.

[0036] Figure 4 The sodium-ion battery cathode material Na is prepared by coating with 2% mixed oxide under the above process conditions. 0.92 (Ni 0.38 Mn 0.45 Ti 0.09 Cu 0.06 Zn 0.02 The coin cell cycle test results for O2 under charge / discharge conditions of 2.0-4.3V showed that the 0.1C charging capacity reached 174.52 mAh / g, and the discharge capacity reached 174.83 mAh / g. The initial efficiency at 0.1C charge / discharge reached 100%, the initial discharge capacity at 1C was 157.98 mAh / g, and the discharge capacity at 1C for 50 cycles was 153.9 mAh / g. The actual retention rate after 50 cycles reached 97.01%. The 1C / 0.1C discharge rate was 90.36%. These results indicate that when the sodium-ion electrode material is coated with a certain amount of nickel, manganese, titanium, copper, and zinc, its 1C cycle retention rate is significantly improved, demonstrating that the coated material has the ability to cycle stably in the battery for a long time.

[0037] Figure 5 The sodium-ion battery cathode material Na is prepared by coating with 2% mixed oxide under the above process conditions. 0.92 (Ni 0.38 Mn 0.45 Ti 0.09 Cu 0.06 Zn 0.02The results of the full electric cycle test of O2 at 25℃ under 2.0-4.25V 1C charge and discharge conditions show that the battery retains 80% of its capacity after 1700 cycles.

[0038] Example 3: S1: First, based on the molecular formula Na of the nano-coating layer... 0.67 (Ni 0.24 Mn 0.55 Ti 0.10 Cu 0.06 Zn 0.05 The molar ratio of nickel, manganese, titanium, copper, and zinc was determined to be 24:55:10:6:5. All raw materials were selected as nanoscale oxides, requiring that the D50 of all oxides be around 50nm, and the particle size of all oxides be as similar as possible. The proportion of each raw material was determined according to the molar ratio of the elements, and after thorough mixing, it was used as a coating material.

[0039] S2: Preparation of Na-based O3 structured sodium-ion layered oxide cathode material for coating 0.94 (Ni 0.32 Mn 0.45 Ti 0.08 Cu 0.15 In the preparation of the cathode material, sodium is replaced with Na2CO3, nickel and manganese are replaced with hydroxide precursors, titanium is replaced with TiO2, copper with CuO, and zinc with ZnO. The weight ratio of the raw materials is determined according to the molar ratio of the elements. After thorough mixing, the mixture is placed in a sintering furnace and sintered in an air atmosphere. The temperature is first raised to 550℃ and held for 5 hours, then raised to 975℃ and held for 15 hours. After cooling in the furnace, the single-crystal sodium-ion layered oxide cathode material is obtained.

[0040] S3: Na, a sodium-coated oxygen cathode material 0.94 (Ni 0.32 Mn 0.45 Ti 0.08 Cu 0.15 The amount of O2 is used as a reference, and the amount of coating material is 2% of the mass of the matrix. After the matrix material and coating material are thoroughly mixed, they are placed in a sintering furnace for sintering.

[0041] S4: Sintering is carried out in an air atmosphere. First, the temperature is raised to 450℃ and held for 3 hours. Then, the temperature is raised to 600℃ and held for 6 hours to obtain sodium-ion layered oxide cathode material coated with P2 phase nano-coating.

[0042] The sodium-ion battery layered oxide cathode material Na, prepared under the above process conditions, is a mixture of nickel, manganese, titanium, copper, and zinc. 0.94 (Ni 0.32 Mn 0.45 Ti 0.08 Cu0.15 The space group of O2 is R-3m, belonging to a rhombohedral lattice crystal with lattice constants: a=b=0.297nm, c=1.61nm, α=β=90°, γ=120°. It is a typical O3 structure. To the left of the first main peak, a small P2 phase diffraction peak appears around 16°. The coated material, under 2.0-4.3V charge-discharge conditions, showed the following results in coin cell tests: 0.1C charging capacity reached 173.62mAh / g, discharge capacity reached 172.83mAh / g, initial discharge capacity at 1C was 157.25mAh / g, and the actual retention rate after 50 cycles at 1C reached 96.4%. Compared with Comparative Example 3, the material coated with the mixed oxide showed a nearly 6 percentage point higher retention rate after 50 cycles at 1C.

[0043] Example 4: S1: First, based on the molecular formula Na of the nano-coating layer... 0.67 (Ni 0.20 Mn 0.55 Ti 0.15 Cu 0.05 Zn 0.05 The molar ratio of nickel, manganese, titanium, copper, and zinc is determined to be 20:55:15:5:5. All raw materials are selected from nanoscale oxides, and the D of all oxides is required to be... 50 All particles are around 50nm, and efforts are made to ensure that the particle size of all oxides is not too different. The proportions of each raw material are determined according to the molar ratio of the elements, and after thorough mixing, they are used as coating materials for later use.

[0044] S2: Preparation of Na-based O3 structured sodium-ion layered oxide cathode material for coating 0.92 (Ni 0.33 Mn 0.54 Cu 0.08 Zn 0.04 In the preparation of the cathode material, sodium is replaced with Na2CO3, nickel and manganese are replaced with hydroxide precursors, copper is replaced with CuO, and zinc is replaced with ZnO. The weight ratio of the raw materials is determined according to the molar ratio of the elements. After thorough mixing, the mixture is placed in a sintering furnace and sintered in an air atmosphere. The temperature is first raised to 550℃ and held for 5 hours, then raised to 975℃ and held for 15 hours. After cooling in the furnace, the single-crystal sodium-ion layered oxide cathode material is obtained.

[0045] S3: Na, a sodium-coated oxygen cathode material 0.92 (Ni 0.33 Mn 0.54 Cu 0.08 Zn 0.04 The amount of O2 is used as a reference, and the amount of coating material is 2% of the mass of the matrix. After the matrix material and coating material are thoroughly mixed, they are placed in a sintering furnace for sintering.

[0046] S4: Sintering is carried out in an air atmosphere. First, the temperature is raised to 450℃ and held for 3 hours. Then, the temperature is raised to 625℃ and held for 6 hours to obtain sodium-ion layered oxide cathode material coated with P2 phase nano-coating.

[0047] The sodium-ion battery layered oxide cathode material Na, prepared under the above process conditions, is a mixture of nickel, manganese, titanium, copper, and zinc. 0.92 (Ni 0.33 Mn 0.54 Cu 0.08 Zn 0.04 The space group of O2 is R-3m, belonging to a rhombohedral lattice crystal with lattice constants: a=b=0.297nm, c=1.61nm, α=β=90°, γ=120°. It is a typical O3 structure. To the left of the first main peak, a small P2 phase diffraction peak appears around 16°. The coated material, under 2.0-4.3V charge-discharge conditions, showed the following results in coin cell tests: 0.1C charging capacity reached 172.46mAh / g, discharge capacity reached 171.69mAh / g, initial discharge capacity at 1C was 155.72mAh / g, and the actual retention rate after 50 cycles at 1C reached 96.7%. Compared with Comparative Example 4, the material coated with the mixed oxide showed a nearly 7 percentage point higher retention rate after 50 cycles at 1C.

[0048] Example 5: S1: First, based on the molecular formula Na of the nano-coating layer... 0.67 (Ni 0.26 Mn 0.55 Ti 0.10 Cu 0.06 Zn 0.03 The molar ratio of nickel, manganese, titanium, copper, and zinc is determined to be 26:55:10:6:3. All raw materials are selected from nanoscale oxides, and the D of all oxides is required to be... 50 All particles are around 50nm, and efforts are made to ensure that the particle size of all oxides is not too different. The proportions of each raw material are determined according to the molar ratio of the elements, and after thorough mixing, they are used as coating materials for later use.

[0049] S2: Preparation of Na1(Ni) matrix O3 structured sodium-ion layered oxide cathode material for coating 0.2 Fe 0.22 Mn 0.45 Cu 0.13In the preparation of the cathode material, sodium is replaced with Na2CO3, nickel and manganese are replaced with hydroxide precursors, copper is replaced with CuO, and zinc is replaced with ZnO. The weight ratio of the raw materials is determined according to the molar ratio of the elements. After thorough mixing, the mixture is placed in a sintering furnace and sintered in an air atmosphere. The temperature is first raised to 550℃ and held for 5 hours, then raised to 925℃ and held for 15 hours. After cooling in the furnace, the single-crystal sodium-ion layered oxide cathode material is obtained.

[0050] S3: Na1(Ni) cathode material with a coated sodium electrode layer. 0.2 Fe 0.22 Mn 0.45 Cu 0.13 The amount of O2 is used as a reference, and the amount of coating material is 2% of the mass of the matrix. After the matrix material and coating material are thoroughly mixed, they are placed in a sintering furnace for sintering.

[0051] S4: Sintering is carried out in an air atmosphere. First, the temperature is raised to 450℃ and held for 3 hours. Then, the temperature is raised to 625℃ and held for 6 hours to obtain sodium-ion layered oxide cathode material coated with P2 phase nano-coating.

[0052] The above-mentioned process conditions yielded a layered oxide cathode material, Na1(Ni), for sodium-ion batteries coated with a mixture of nickel, manganese, titanium, copper, and zinc. 0.2 Fe 0.22 Mn 0.45 Cu 0.13 The space group of O2 is R-3m, belonging to a rhombohedral lattice crystal with lattice constants: a=b=0.297nm, c=1.61nm, α=β=90°, γ=120°. It is a typical O3 structure. To the left of the first main peak, a small P2 phase diffraction peak appears around 16°. The coated material, under 2.0-4.3V charge-discharge conditions, showed the following results in coin cell tests: 0.1C charging capacity reached 178.6mAh / g, discharge capacity reached 174.5mAh / g, initial discharge capacity at 1C was 144.2mAh / g, and the actual retention rate after 50 cycles at 1C reached 96.3%. Compared with Comparative Example 3, the material coated with the mixed oxide showed an 8 percentage point higher retention rate after 50 cycles at 1C.

[0053] Comparative Example 1: S1: Preparation of Na, a sodium-ion layered oxide cathode material with an O3 matrix structure, for coating. 0.92 (Ni 0.38 Mn 0.45 Ti 0.09 Cu 0.06 Zn 0.02In the preparation of the cathode material, sodium is replaced by Na2CO3, nickel and manganese by hydroxide precursors, titanium by TiO2, copper by CuO, and zinc by ZnO. The weight ratio of the raw materials is determined according to the molar ratio of the elements. After thorough mixing, the mixture is placed in a sintering furnace and sintered in an air atmosphere. The temperature is first raised to 550℃ and held for 5 hours, then raised to 950℃ and held for 15 hours. After cooling in the furnace, the single-crystal sodium-ion layered oxide cathode material is obtained.

[0054] S2: The coating material is AlPO4, with the sodium electrode layer containing Na as the coating material. 0.92 (Ni 0.38 Mn 0.45 Ti 0.09 Cu 0.06 Zn 0.02 Using the amount of O2 as a reference, the weight percentage of the coating material and the matrix is ​​1%. After the matrix material and the coating material are fully mixed, they are placed in a sintering furnace for sintering.

[0055] S3: Sintering is carried out in an air atmosphere. First, the temperature is raised to 450℃ and held for 3 hours. Then, the temperature is raised to 650℃ and held for 6 hours to obtain sodium-ion layered oxide cathode material coated with nano-coating.

[0056] Figure 6 The sodium-ion battery layered oxide cathode material Na, coated with AlPO4, was prepared under the above process conditions. 0.92 (Ni 0.38 Mn 0.45 Ti 0.09 Cu 0.06 Zn 0.02 The X-ray diffraction pattern of O2 shows that the space group of the main phase of the coated sodium-ion battery cathode material is R-3m, belonging to a rhombohedral lattice crystal with lattice constants: a=b=0.297nm, c=1.61nm, α=β=90°, γ=120°. This is a typical O3 structure. To the left of the first main peak, near 16°, a very small diffraction peak appears. This peak matches well with the strongest peak of the P2 phase, likely indicating that the mixed oxide reacted in situ with residual sodium on the oxygen layer surface during coating, forming a sodium-deficient P2 phase. Besides a small amount of sodium-ion battery oxygen P2 phase, a very small amount of other impurity phases also appeared, possibly a nickel-manganese mixed oxide (Ni... 0.75 Mn 0.25 )O.

[0057] Figure 7 Na is the sodium-ion battery cathode material prepared by coating with 1% AlPO4 under the above process conditions. 0.92 (Ni 0.38 Mn 0.45 Ti 0.09 Cu 0.06Zn 0.02 The results of coin cell tests using O2 under charge / discharge conditions of 2.0-4.3V show the following: 0.1C charging capacity reaches 156.64 mAh / g, discharge capacity reaches 162.85 mAh / g, initial efficiency at 0.1C is 103.96%, initial discharge capacity at 1C is 144.91 mAh / g, discharge capacity at 1C for 50 cycles is 131.04 mAh / g, and the actual retention rate after 50 cycles reaches 90.43%. The 1C / 0.1C discharge rate is 89.0%. These results indicate that when the sodium electrode layer oxygen cathode material is coated with a certain amount of AlPO4, its overall coin cell performance is not ideal, even inferior to the uncoated substrate material. The coating does not achieve the goal of improving the material's cycle stability.

[0058] Comparative Example 2: S1: Preparation of Na, a sodium-ion layered oxide cathode material with an O3 matrix structure, for coating. 0.92 (Ni 0.38 Mn 0.45 Ti 0.09 Cu 0.06 Zn 0.02 In the preparation of the cathode material, sodium is replaced by Na2CO3, nickel and manganese by hydroxide precursors, titanium by TiO2, copper by CuO, and zinc by ZnO. The weight ratio of the raw materials is determined according to the molar ratio of the elements. After thorough mixing, the mixture is placed in a sintering furnace and sintered in an air atmosphere. The temperature is first raised to 550℃ and held for 5 hours, then raised to 950℃ and held for 15 hours. After cooling in the furnace, the single-crystal sodium-ion layered oxide cathode material is obtained.

[0059] S2: The coating material is Mn2O3, with the sodium electrode layer containing Na as the coating material. 0.92 (Ni 0.38 Mn 0.45 Ti 0.09 Cu 0.06 Zn 0.02 Using the amount of O2 as a reference, the weight percentage of the coating material and the matrix is ​​2%. After the matrix material and the coating material are fully mixed, they are placed in a sintering furnace for sintering.

[0060] S3: Sintering is carried out in an air atmosphere. First, the temperature is raised to 450℃ and held for 3 hours. Then, the temperature is raised to 650℃ and held for 6 hours to obtain sodium-ion layered oxide cathode material coated with nano-coating.

[0061] Figure 8 The Na+ layered oxide cathode material for sodium-ion batteries, coated with Mn2O3, was prepared under the above process conditions. 0.92 (Ni 0.38 Mn 0.45 Ti 0.09 Cu0.06 Zn 0.02 The X-ray diffraction pattern of O2 shows that the space group of the main phase of the coated sodium-ion battery cathode material is R-3m, belonging to a rhombohedral lattice crystal with lattice constants: a=b=0.297nm, c=1.61nm, α=β=90°, γ=120°. This is a typical O3 structure. To the left of the first main peak, near 16°, a very small diffraction peak appears. This peak matches well with the strongest peak of the P2 phase, indicating that during coating, Mn2O3 reacted in situ with residual sodium on the oxygen layer surface to form a sodium-manganese-based P2 phase.

[0062] Figure 9 Na is the sodium-ion battery cathode material prepared by coating with 2% Mn2O3 under the above process conditions. 0.92 (Ni 0.38 Mn 0.45 Ti 0.09 Cu 0.06 Zn 0.02 The results of the coin cell test under charge-discharge conditions of O2 at 2.0-4.3V show that the charging capacity at 0.1C reached 176.64 mAh / g, the discharging capacity reached 170.0 mAh / g, the initial efficiency at 0.1C reached 96.81%, the initial discharge capacity at 1C was 156.94 mAh / g, the discharge capacity at 1C for 50 cycles was 150.89 mAh / g, and the actual retention rate after 50 cycles reached 96.1%. The 1C / 0.1C discharge rate was 91.7%. These results indicate that when the sodium electrode layer oxygen cathode material is coated with a certain amount of Mn2O3, its overall electrochemical performance for coin cell charging is excellent, and the 50-cycle retention rate at 1C is close to the results of Example 2. From the coin cell charging results, the coating effect is significant.

[0063] Figure 10 Na is a sodium-ion battery cathode material prepared by coating with 2% Mn2O3. 0.92 (Ni 0.38 Mn 0.45 Ti 0.09 Cu 0.06 Zn 0.02 The results of full-electric cycling of O2 under charge-discharge conditions of 2.0-4.25V 1C are shown. The full-electric cycling curves reveal that the cycling stability of the sodium-coated oxygen cathode material obtained from Mn2O3 coating is significantly lower than that of Example 2. This material exhibits a noticeable drop in stability after more than 800 cycles, which may be due to the insufficient stability of the P2 phase structure formed by sodium and manganese.

[0064] Comparative Example 3: S1: Preparation of Na, a sodium-ion layered oxide cathode material with an O3 matrix structure, for coating. 0.94 (Ni 0.32 Mn0.45 Ti 0.08 Cu 0.15 In the preparation of the cathode material, sodium is replaced with Na2CO3, nickel and manganese are replaced with hydroxide precursors, titanium is replaced with TiO2, and copper is replaced with CuO. The weight ratio of the raw materials is determined according to the molar ratio of the elements. After thorough mixing, the mixture is placed in a sintering furnace and sintered in an air atmosphere. The temperature is first raised to 550℃ and held for 5 hours, then raised to 950℃ and held for 15 hours. After cooling in the furnace, the single-crystal sodium-ion layered oxide cathode material is obtained.

[0065] S2: The coating material is Al2O3, with the sodium electrode layer containing oxygen as the coating material. 0.94 (Ni 0.32 Mn 0.45 Ti 0.08 Cu 0.15 Using the amount of O2 as a reference, the weight percentage of the coating material and the matrix is ​​1%. After the matrix material and the coating material are fully mixed, they are placed in a sintering furnace for sintering.

[0066] S3: Sintering is carried out in an air atmosphere. First, the temperature is raised to 450℃ and held for 3 hours. Then, the temperature is raised to 600℃ and held for 6 hours to obtain sodium-ion layered oxide cathode material coated with nano-coating.

[0067] The sodium-ion battery layered oxide cathode material Na, prepared under the above process conditions, is a mixture of nickel, manganese, titanium, copper, and zinc. 0.94 (Ni 0.32 Mn 0.45 Ti 0.08 Cu 0.15 The space group of O2 is R-3m, belonging to a rhombohedral lattice crystal with lattice constants: a=b=0.297nm, c=1.61nm, α=β=90°, γ=120°. It is a typical O3 structure. To the left of the first main peak, a small P2 phase diffraction peak appears around 16°. The coated material, under 2.0-4.3V charge-discharge conditions, showed the following results: 0.1C charging capacity reached 168.6mAh / g, discharge capacity reached 167.4mAh / g, initial discharge capacity at 1C was 150.5mAh / g, and the actual retention rate after 50 cycles at 1C reached 90.3%.

[0068] Comparative Example 4: S1: Preparation of Na, a sodium-ion layered oxide cathode material with an O3 matrix structure, for coating. 0.92 (Ni 0.33 Mn 0.54 Cu 0.08 Zn 0.04In the preparation of the cathode material, sodium is replaced with Na2CO3, nickel and manganese are replaced with hydroxide precursors, zinc is replaced with ZnO, and copper is replaced with CuO. The weight ratio of the raw materials is determined according to the molar ratio of the elements. After thorough mixing, the mixture is placed in a sintering furnace and sintered in an air atmosphere. The temperature is first raised to 550℃ and held for 5 hours, then raised to 950℃ and held for 15 hours. After cooling in the furnace, the single-crystal sodium-ion layered oxide cathode material is obtained.

[0069] S2: The coating material is WO3, with the sodium electrode layer containing Na as the coating material. 0.92 (Ni 0.33 Mn 0.54 Cu 0.08 Zn 0.04 Using the amount of O2 as a reference, the weight percentage of the coating material and the matrix is ​​1%. After the matrix material and the coating material are fully mixed, they are placed in a sintering furnace for sintering.

[0070] S3: Sintering is carried out in an air atmosphere. First, the temperature is raised to 450℃ and held for 3 hours. Then, the temperature is raised to 600℃ and held for 6 hours to obtain sodium-ion layered oxide cathode material coated with nano-coating.

[0071] The sodium-ion battery layered oxide cathode material Na, prepared under the above process conditions, is a mixture of nickel, manganese, titanium, copper, and zinc. 0.92 (Ni 0.33 Mn 0.54 Cu 0.08 Zn 0.04 The space group of O2 is R-3m, belonging to a rhombohedral lattice crystal with lattice constants: a=b=0.297nm, c=1.61nm, α=β=90°, γ=120°. It is a typical O3 structure. To the left of the first main peak, a small P2 phase diffraction peak appears around 16°. The coated material, under 2.0-4.3V charge-discharge conditions, showed the following results: 0.1C charging capacity reached 169.5mAh / g, discharge capacity reached 167.8mAh / g, initial discharge capacity at 1C was 148.3mAh / g, and the actual retention rate after 50 cycles at 1C reached 89.5%.

[0072] Comparative Example 5: S1: Preparation of Na1(Ni) matrix O3 structured sodium-ion layered oxide cathode material for coating 0.2 Fe 0.22 Mn 0.45 Cu 0.13In the preparation of the cathode material, sodium is replaced by Na2CO3, nickel, iron, and manganese are replaced by hydroxide precursors, and copper is replaced by CuO. The weight ratio of the raw materials is determined according to the molar ratio of the elements. After thorough mixing, the mixture is placed in a sintering furnace and sintered in an air atmosphere. The temperature is first raised to 550℃ and held for 5 hours, then raised to 950℃ and held for 15 hours. After cooling in the furnace, the single-crystal sodium-ion layered oxide cathode material is obtained.

[0073] S2: The coating material is ZrO2, with the sodium electrode layer containing oxygen cathode material Na1 (Ni) as the coating. 0.2 Fe 0.22 Mn 0.45 Cu 0.13 Using the amount of O2 as a reference, the weight percentage of the coating material and the matrix is ​​1%. After the matrix material and the coating material are fully mixed, they are placed in a sintering furnace for sintering.

[0074] S3: Sintering is carried out in an air atmosphere. First, the temperature is raised to 450℃ and held for 3 hours. Then, the temperature is raised to 600℃ and held for 6 hours to obtain sodium-ion layered oxide cathode material coated with nano-coating.

[0075] The above-mentioned process conditions yielded a layered oxide cathode material, Na1(Ni), for sodium-ion batteries coated with a mixture of nickel, manganese, titanium, copper, and zinc. 0.2 Fe 0.22 Mn 0.45 Cu 0.13 The space group of O2 is R-3m, belonging to a rhombohedral lattice crystal with lattice constants: a=b=0.297nm, c=1.61nm, α=β=90°, γ=120°. It is a typical O3 structure. To the left of the first main peak, a small P2 phase diffraction peak appears around 16°. The coated material, under 2.0-4.3V charge-discharge conditions, showed the following results: 0.1C charging capacity reached 168.4mAh / g, discharge capacity reached 165.7mAh / g, initial discharge capacity at 1C was 144.0mAh / g, and the actual retention rate after 50 cycles at 1C reached 88.3%.

[0076] Table 1. Comparison of Electrochemical Performance of Examples and Comparative Examples (2.0-4.3V Charge / Discharge Data) Table 1 leads to the conclusion that the main difference in cycle retention rate of the O3-structured layered oxide cathode material in sodium-ion batteries after coating lies in its cycle retention rate. In the comparative examples, except for the manganese trioxide coating, the 1C50-cycle retention rate at 4.3V is generally below 91%, with the lowest being only 88.3%. Such a retention rate typically results in no more than 500 cycles at a full charge of 4.25V. While the manganese trioxide coating achieves 96.1% 1C50-cycle retention rate at 4.3V, a significant drop occurs around 900 cycles at full charge, indicating that the structural stability of the coating layer still has issues. In the examples, the nickel-manganese-titanium-copper oxide coating, with a coating amount of 2% or more, achieves a 1C50-cycle retention rate of over 96%. Comparative Example 2 achieves over 1700 cycles at 4.25V full charge, fully meeting the requirements of power batteries. Comparing the effects of all the nickel-manganese-titanium-copper hybrid coating materials of this invention with other materials, the advantages of this invention are very obvious.

[0077] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A P2 phase nanocoating layer, characterized in that, Its molecular formula is Na a (Ni x Mn y Ti z A 1-x-y-z O2, where 0.5≤a≤0.85, 0.1≤x≤0.3, 0.5≤y≤0.7, 0.05≤z≤0.2, and A=Ca, Mg, Cu or Zn.

2. The application of the P2 phase nanocoating layer as described in claim 1 in the preparation of sodium-electric layered oxide cathode materials.

3. A method for coating sodium-ion battery layered oxide cathode material with a nickel-manganese-titanium-copper mixture, characterized in that, The specific steps are as follows: S1. First, determine the molar ratio of each element according to the molecular formula of the aforementioned P2 phase nanocoating layer, then determine the weight ratio of the raw materials containing these elements, mix them thoroughly, and obtain the nanocoating material. S2. The nano-coating material is thoroughly mixed with the O3 structure matrix and sintered. The nano-coating material reacts in situ with the residual sodium on the surface of the O3 structure matrix to obtain a sodium-electric layered oxide cathode material coated with the aforementioned P2 phase nano-coating layer.

4. The method according to claim 3, characterized in that, In step S1, the raw material is an oxide, hydroxide, or carbonate.

5. The method according to claim 3, characterized in that, In step S1, the particle size of the raw material is no greater than 200 nm.

6. The method according to claim 3, characterized in that, In step S2, the matrix is ​​selected from any of the following: Na 0.92 (Ni 0.38 Mn 0.45 Ti 0.09 Cu 0.06 Zn 0.02 O2, Na 0.94 (Ni 0.32 Mn 0.45 Ti 0.08 Cu 0.15 O2, Na 0.92 (Ni 0.33 Mn 0.54 Cu 0.08 Zn 0.04 )O2, Na1(Ni 0.2 Fe 0.22 Mn 0.45 Cu 0.13 )O2.

7. The method according to claim 3, characterized in that, In step S2, the amount of nano-coating material used is 0.3 to 5% of the matrix mass.

8. The method according to claim 3, characterized in that, In step S2, sintering is carried out in an air or oxygen atmosphere.

9. The method according to claim 3, characterized in that, In step S2, the sintering conditions are as follows: first, heat to 300-450℃ and hold for 1.5-4 hours, then heat to 550-700℃ and hold for 5-10 hours.